Eco-sustainable systems based on poly(lactic acid), diatomite and coffee grounds extract for food packaging - Cacciotti, Ilaria; Mori, Stefano; Cherubini, Valeria; Nanni, Francesca (Elsevier, 2018)
In the food packaging sector many efforts have been (and are) devoted to the development of new materials in order to reply to an urgent market demand for green and eco-sustainable products. Particularly a lot of attention is currently devoted both to the use of compostable and biobased polymers as innovative and promising alternative to the currently used petrochemical derived polymers, and to the re-use of waste materials coming from agriculture and food industry. In this work, multifunctional eco-sustainable systems, based on poly(lactic acid) (PLA) as biopolymeric matrix, diatomaceous earth as reinforcing filler and spent coffee grounds extract as oxygen scavenger, were produced for the first time, in order to provide a simultaneous improvement of mechanical and gas barrier properties. The influence of the diatomite and the spent coffee grounds extract on the microstructural, mechanical and oxygen barrier properties of the produced films was deeply investigated by means of X-Ray diffraction (XRD), infrared spectroscopy (FT-IR, ATR), scanning electron microscopy (SEM), uniaxial tensile tests, O2 permeabilimetry measurements. An improvement of both mechanical and oxygen barrier properties was recorded for systems characterised by the co-presence of diatomite and coffee grounds extract, suggesting a possible synergic effect of the two additives.
Keywords: Polylactic (acid); Diatomite; Spent coffee grounds extract; Microstructure; Mechanical properties; Thermal properties